KNOWLEDGE OF REPRODUCTIVE HEALTH WITH FAMILY PREPARATION IN MIDWIFERY STUDENTS: KNOWLEDGE OF REPRODUCTIVE HEALTH WITH FAMILY PREPARATION IN MIDWIFERY STUDENTS - Anggraini, Dina Dewi; Yanik Muyassaroh; Aulia Fatmayanti (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2024)
Background: Reproductive health is an important aspect of family life. Midwifery students, as prospective reproductive health workers, need to have adequate knowledge about reproductive health to prepare themselves for family life. This study aims to analyze the relationship between reproductive health knowledge and preparation for family in midwifery students. Method: This study used a cross-sectional design with a sample of 61 final year midwifery students taken using a total sampling technique. The instrument used in the research was a questionnaire. Data were analyzed using the Chi-Square test. Results: The results of the study show that there is a significant relationship between reproductive health knowledge and family preparation among midwifery students in terms of age at family (p value 0.001), pregnancy spacing (p value 0.000), and participation in family planning programs (p value 0.003). Conclusion: Good reproductive health knowledge is related to good family preparation in students. This shows the importance of reproductive health education for students to prepare themselves for family life.